Implementing Cloud Computing in Companies to Increase Business Efficiency - Dwi Yuniarto (Jurnal Info Sains : Informatika dan Sains, 2023)
Cloud computing has emerged as an attractive solution for companies looking to increase operational flexibility, reduce infrastructure costs, and improve business performance. Through comprehensive analysis of primary and secondary data, this research aims to evaluate the impact of implementing cloud computing in various corporate sectors. This research aims to investigate the application of cloud computing technology in a corporate environment as a strategy to increase business efficiency. This research uses a qualitative approach with descriptive methods. The research results show that the use of cloud computing services has had a significant positive impact on various business entities and organizations. The use of cloud computing helps optimize operational cost efficiency by reducing the need for expensive physical infrastructure, while providing high scalability and strong data security. Additionally, integration between cloud computing and the Internet of Things (IoT) has enabled efficient data collection and analysis remotely, facilitated effective cross-divisional collaboration, and enabled the development of complex projects. Overall, the results of this research emphasize the importance of adopting cloud computing as a crucial technological foundation for innovation and business growth in today's digital era.